Visit to Universitas Muhammadiyah Yogyakarta (UMY) - strengthening academic ties and community engagement / Muhamad Faizal Pakir Mohamed Latiff - Pakir Mohamed Latiff, Muhamad Faizal (UiTM Global @ Office of International Affairs, 2024)
From 5 to 11 May 2024, a group of academics from several Malaysian universities visited Universitas Muhammadiyah Yogyakarta (UMY) as part of an initiative to foster international collaboration and engage in community service. The delegation included representatives from Universiti Teknologi MARA (UiTM), Universiti Sains Malaysia (USM), Universiti Putra Malaysia (UPM), Universiti Malaya (UM), and professionals from the private sector. The focus of the visit was on academic exchange and community outreach, particularly in the field of water resource management.